Effectiveness of Cabergoline Treatment in Patients with Acromegaly Uncontrolled with SSAs: Experience of a Single Tertiary Center - Sahin, Serdar; Fidan, Mehmet Cem; Korkmaz, Ozge Polat; Durcan, Emre; Ozkaya, Hande Mefkure; Kadioglu, Pinar (Experimental and Clinical Endocrinology & Diabetes, 2020)
Purpose To evaluate the effectiveness of cabergoline and the parameters affecting cabergoline response as add-on treatment to somatostatin analaogues (SSA) in patients with acromegaly uncontrolled with SSAs.Material and Method One hundred and twenty-nine acromegalic patients uncontrolled with SSA who had cabergoline added to their treatment were included in this retrospective study. Patients were divided into the SSAs + cabergoline-responsive (group 1) and non-responsive groups (group 2), and biochemical, pathologic, and radiologic parameters were assessed.Results IGF-1 normalization was achieved in 75 of 129 patients (58%) when cabergoline was added to the SSA treatment. Female patients were significantly higher in group 1 compared to group 2 (p=0.006). Group 1 had significantly smaller pre- and post-cabergoline tumor size (p=0.011, p=0.007 respectively), lower levels of IGF-1 in pre-and post-operative period (p=0.040, p=0.001), and lower levels of IGF-1 in pre- and post-cabergoline treatment (p<0.001). Cavernous invasion on sellar magnetic resonance imaging, dural invasion in pathologic examination were not significantly different between the groups. Sellar invasion in pathologic examination was significantly higher in group 1 (p=0.011). No significant difference was found in proliferation indices between two groups. The presence of fibrous bodies was significantly lower in group 1 (p=0.010).Conclusion Cabergoline can be added to the treatment of acromegalic patients uncontrolled with SSAs due to its ease of use and low economic cost, especially in patients with acromegaly who have small adenomas and no fibrous bodies.
Keywords: Acromegaly; cabergoline; combined therapy; somatostatin analogue